Tax Aggressiveness: Tinjauan Leverage, Financial Distress, Capital Intensity Ratio, dan ICSR dengan Pemoderasi Ukuran Perusahaan (Jurnal Ekonomi dan Bisnis Islam, 2024)
AbstractThis research aims to explore the impact of leverage, financial distress, capital intensity ratio, and Islamic Corporate Social Responsibility (ICSR) on tax aggressiveness by using company size as a moderating variable in consumer goods companies listed on the IDX during the 2020-2022 period. This research adopts a quantitative approach in associative research type, relying on data taken from company annual reports. The sampling method used purposive sampling, resulting in 53 companies as samples. This research findings show that leverage, financial distress, and capital intensity ratio significantly influence tax aggressiveness, while Islamic Corporate Social Responsibility (ICSR) has no effect. Apart from that, company size can’t moderate or weaken the influence of leverage on tax aggressiveness but company size can moderate or strengthen the influence of financial distress, capital intensity ratio, and ICSR on tax aggressiveness.Keywords: Leverage; Financial Distress; Capital Intensity Ratio; ICSR; Tax Aggressiveness. AbstrakTujuan dari penelitian ini ialah mengeksplorasi dampak leverage, financial distress, capital intensity ratio, dan Islamic Corporate Social Responsibility (ICSR) terhadap tax aggressiveness dengan menggunakan ukuran perusahaan sebagai variabel moderasi pada perusahaan consumer goods yang terdaftar di BEI selama periode 2020-2022. Penelitian ini mengadopsi pendekatan kuantitatif dalam jenis penelitian asosiatif, mengandalkan data yang diambil pada laporan tahunan perusahaan. Metode penarikan sampel menggunakan pusposive sampling, menghasilkan 53 perusahaan sebagai sampel. Temuan penelitian menunjukkan bahwa leverage, financial distress, dan capital intensity ratio memiliki pengaruh terhadap tax aggressiveness, sementara Islamic Corporate Social Responsibility (ICSR) tidak berpengaruh. Selain itu, ukuran perusahaan tidak mampu memoderasi atau memperlemah pengaruh leverage terhadap tax aggressiveness, tetapi mampu memoderasi atau memperkuat pengaruh financial distress, capital intensity ratio, dan ICSR terhadap tax aggressiveness.Kata Kunci: Leverage; Financial Distress; Capital Intensity Ratio; ICSR; Tax Aggressiveness.